Contributions of Design in the resignification of the school environment: Application of research instruments to give voice to students - Avila , Bruna Fagundes de; Dresch , Nelton Luis; Roldo , Liane (Seven Editora, 2023)
Education based on hierarchical and passive teaching in relation to student participation no longer seems to be sufficient to guarantee learning. Several initiatives have sought to enhance educational processes based on project-based teaching and problem solving. This research is based on concepts such as Participatory Design and Project-Based Learning, used as auxiliary tools to the learning processes for the final grades of Elementary School in the after-school period, in a school on the outskirts of the city of Porto Alegre, RS. In this research, the application of two qualitative data collection instruments is presented. One of them applied after the first month of activities, based on an instrument developed by the Porvir Institute, where students talk about happiness in the educational environment. The other applied after seven months of research, and in it, students gain a voice about the Design laboratories they were part of. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-179